AB0675 Cardiovascular risk assessment in systemic lupus erythematosus patients using the south european and spanish score charts. (23rd January 2014) - Rosales Alexander, J.L.; Galindo, M.; Magro Checa, C.; Mateo, I.; Raya Alvarez, E.; Carreira, P.E.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with increased risk for accelerated atherosclerosis and coronary artery disease. SLE patients have a bimodal mortality pattern, the later one being associated with myocardial infarction. It has been suggested that some disease characteristics as well as treatments could play a role in the accelerated atherosclerotic process. EULAR has published some evidence-based recommendations for cardiovascular (CV) risk assessment in rheumatoid arthritis (RA) and other inflammatory arthritis, but there are no recommendations for SLE patients. Objectives: To assess CV risk in SLE patients comparing two different scores: the South European SCORE chart (Eu-SCORE) and the SCORE chart calibrated for Spain (S-SCORE), and to analyze clinical characteristics predicting a higher CV global risk. Methods: Patients fulfilling the ACR revised classification criteria for SLE were prospectively included in a database created in 1995 at the "Doce de Octubre" hospital, containing demographic and clinical information. For the study, 150 living Spanish patients were selected. Classical CV risk factors, previous ischemic events, acute phase reactants and lipid profile were obtained, and CV risk was calculated with both charts. Chi-square or McNemar's tests were used to assess differences between qualitative variables, and ANOVA with Bonferroni adjustment for comparing means. Factors predicting higher global CV risk were evaluated by multivariate lineal regression analysis. Results: Most patients (88%) were women. Mean age was 49±14 years and mean disease duration was 19±9 years. Mean Eu-SCORE was 1±1.7 and mean S-SCORE was 1.4±2. Using the Eu-SCORE: low, intermediate and high CV risk were found in 115(77%), 21(14%) and 14(9%) respectively. Using the S-SCORE: low, intermediate and high risk were found in 105(70%), 24(16%) and 21(14%) respectively (p<0, 001). Besides classical CV risk factors, higher global CV risk (using the S-SCORE) was associated with higher disease duration and renal involvement. Conclusions: In our study most SLE patients have low and intermediate CV risk. S-SCORE overestimates CV risk compared to Eu-SCORE. However, the overall CV risk using both SCORE charts is low in these patients known to have increased CV morbidity/mortality, suggesting the need of other complementary methods to assess the true CV risk. Higher global CV risk is associated in our SLE group with renal involvement and higher disease duration, suggesting that not only classic CV risk factors, but also inflammatory changes and cumulative damage might contribute to the global CV risk in SLE patients. References: Frostegård J. Systemic lupus erythematosus and cardiovascular disease. Lupus. 2008 May; 17(5):364-7. Bengtsson C, Ohman ML, Nived O, Rantapää Dahlqvist S. Cardiovascular event in Systemic Lupus Erythematosus in northern Sweden - Incidence and predictors in a 7-year follow up study. Lupus. 2011 Nov 7. Disclosure of Interest: None Declared